Akibat Hukum Pembubaran Koperasi Terhadap Hak dan Kewajiban Anggota - Riandy Arya Satria; I Nyoman Putu Budhiarta; Ni Gusti Ketut Sri Astiti (Jurnal Preferensi Hukum, 2021)
In running a cooperative business, of course, the ups and downs of the economic situation greatly affect the profit and loss of a business, in the ups and downs the cooperative can develop and develop its business so that it gets bigger, but in the ebb and flow conditions the cooperative can also experience losses that will have an impact on business continuity to cause the cooperative to go bankrupt or dissolution of the cooperative. The dissolution of a cooperative certainly has legal consequences for both the management and the members. The purpose of this study was to determine the legal consequences of the dissolution of the cooperative on the rights and obligations of members. This study uses normative research with a statutory approach, a conceptual approach, and a case approach. Sources of legal materials used in the form of secondary, primary and tertiary legal sources and then analyzed descriptively. The results of the study reveal that the legal consequences that occur after the dissolution of the cooperative, namely the cooperative legal entity must be settled, operational transactions are terminated, employees can be terminated, members can no longer resign, the powers of the cooperative apparatus are frozen and are also replaced by liquidators, and management and supervisors can be held accountable both civilly and criminally if it is proven that due to their mistakes and negligence the cooperative has gone bankrupt. In addition, the legal entity of the cooperative will also be deleted